The Importance Of Laboratory Training In Biological Science Teaching - Dilnavoz Bakturdievna Saidova (Academia One Publishing, 2023)
The article presents the practical importance of pedagogical technologies in the organization of laboratory classes in biological sciences.
Keywords: Lobarator; experimental